Factors influencing aggressive tax planning among companies listed on the ace market: The moderating effect of non-audit services fee - Rosmaria, Jaffar @ Harun (2022)
Globally, aggressive tax planning (ATP) has been acknowledged as an ongoing serious concern as it affects government coffers. Therefore, governments have to confront the issues of ATP to avoid huge losses in government revenue. The major purpose of this study is to investigate the factors that contribute to ATP conducted by companies listed on the ACE Market in Bursa Malaysia. This study empirically examines the relationships between company size, profitability, leverage, capital intensity, inventory intensity, financial distress and ethnicity and ATP. As a new contribution to ATP knowledge, the moderating effect of non-audit services (NAS) fee on the relationships is also examined. Data was obtained from DataStream software and companies’ annual reports. Using panel data analysis, the findings showed that profitability and financial distress had significant relationships with ATP. Meanwhile, other variables, namely company size, leverage, capital intensity, inventory intensity, and ethnicity, were insignificant and were not associated with ATP. Additionally, this study provided evidence that integrating the NAS fee as a moderator strengthened the ability of the model to explain the predictors of ATP. The result showed that the NAS fee significantly moderates the relationships between all the variables investigated and ATP, except for capital intensity. This study concluded that profitability and financial distress were the most influential factors that contribute to ATP among companies listed on the ACE Market. NAS fees also played a significant role in moderating certain factors towards ATP. Consequently, the results of this study provide insights to the authority on the factors that influence ATP and could be useful in formulating regulations that minimise potential tax revenue losses.